Adverse childhood experiences as risk factors for recurrent admissions in young psychiatric inpatients - Fellinger, Matthäus; Knasmüller, Philipp; Kocsis-Bogar, Krisztina; Wippel, Andreas; Fragner, Laura; Mairhofer, Dunja; Hochgatterer, Paulus; Aigner, Martin (Frontiers in Psychiatry, 2022)
Background Patients who require psychiatric inpatient treatment early in life are a particularly at-risk population. Factors such as adverse childhood experiences (ACEs) are, however, not well studied in those requiring psychiatric inpatient treatment during both childhood or adolescence and adulthood. Thus, the aim of the current study was to investigate, in young adult inpatients, the risk factors for prior admissions in Child and Adolescent Psychiatry, with a focus on ACEs. Materials and methods An explorative population-based systematic chart investigation of psychiatric inpatients aged 18–25 was conducted at the University Hospital Tulln, Austria. Data analysis was done with descriptive methods and Pearson’s chi- squared-, Fisher’s exact-, Mann–Whitney-U-tests and predictive logistic regression models. Results The sample comprised 390 inpatients (51.8% female), with an average age of 20 years at first psychiatric hospital admission. Those with a former child and adolescent psychiatry inpatient treatment (10.3%) were predominantly female (77.5%). Their number of documented ACEs was increased compared to those without former child and adolescent psychiatry admissions (2 vs 1.1), with up to twice as many experiences of family dysfunction, neglect or abuse. Sexual abuse (OR: 3.0), having been an adopted or fostered child (OR: 4.5), and female sex (OR: 3.0) were identified as main risk factors. Furthermore, former child and adolescent psychiatry inpatients suffered from higher rates of psychosomatic or personality disorders, comorbidities and functional impairment, and were readmitted twice as often in young adulthood. Conclusion Young adult inpatients with reoccurring psychiatric inpatient treatments have increased rates of severe ACEs. Thus, special attention should be given to identifying ACEs, evaluating needs for psychosocial support and therapy, and meeting these needs after discharge.